Long COVID and gut microbiome: insights into pathogenesis and therapeutics - Raphaela I. Lau; Qi Su; Siew C. Ng (Gut Microbes)
Post-acute coronavirus disease 2019 syndrome (PACS), following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection or coronavirus disease 2019 (COVID-19), is typically characterized by long-term debilitating symptoms affecting multiple organs and systems. Unfortunately, there is currently a lack of effective treatment strategies. Altered gut microbiome has been proposed as one of the plausible mechanisms involved in the pathogenesis of PACS; extensive studies have emerged to bridge the gap between the persistent symptoms and the dysbiosis of gut microbiome. Recent clinical trials have indicated that gut microbiome modulation using probiotics, prebiotics, and fecal microbiota transplantation (FMT) led to improvements in multiple symptoms related to PACS, including fatigue, memory loss, difficulty in concentration, gastrointestinal upset, and disturbances in sleep and mood. In this review, we highlight the latest evidence on the key microbial alterations observed in PACS, as well as the use of microbiome-based therapeutics in managing PACS symptoms. These novel findings altogether shed light on the treatment of PACS and other chronic conditions.